The Relationship between the Role of the Family and the Incident of Wasting in Toddlers in the Working Area of the Pulo Lor Health Center, Jombang Regency - Ratna Dewi Permatasari; Henny Sulistyawati; Yana Eka Mildiana (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2024)
The toddler years are a very important period of life where a very rapid growth and development process occurs, namely physical growth and psychomotor, mental, and social development. Nowadays, the problem of malnutrition in toddlers, especially aged 1-5 years, is very serious and needs further treatment. Some literature states that the role of the family, especially family parenting, plays a very important role in the problem of providing nutrition during the toddler years. Providing quality supplementary food/PMT is a solution that must be implemented by parents who have children with nutritional problems. The role of families who do not pay attention to their toddler's diet has an impact on eating patterns that are not by the child's nutritional needs, thus having an effect on the health status of toddlers. This research design uses analytical methods with a Cross Sectional approach. The sampling method was carried out by Total Random Sampling. The independent variable is the role of the family and the dependent variable is the incidence of malnutrition. Research data was collected using a questionnaire and by looking at the KMS book for toddlers. After the questionnaire data was collected, tabulation was carried out and statistical tests were carried out using the Spearman Rank test with a significance level of α = 0.05. The results of the study showed that the role of the family was the highest at 42 families (48.8%), and the eating patterns of children under five were mostly in the category of 38 children under five (44.2%). From the results of statistical analysis using the Spearman Rank test, the value ρ = 0.014 < α = 0.05 was obtained. The role of the family is related to the incidence of malnutrition in toddlers aged 1-5 years. Providing health education to families is very important in terms of providing quality supplementary food/PMT to increase family knowledge in feeding children to avoid malnutrition.